Analysis of strain relaxation process in GaInN/GaN heterostructure by in situ X‐ray diffraction monitoring during metalorganic vapor‐phase epitaxial growth. Issue 3 (30th January 2013) - Iida, Daisuke; Kondo, Yasunari; Sowa, Mihoko; Sugiyama, Toru; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu
Abstract Strain relaxation in a GaInN/GaN heterostructure is analyzed by combining in situ X‐ray diffraction (XRD) monitoring and ex situ observations. Two different characteristic thicknesses of GaInN films are defined by the evolution of in situ XRD from the full width at half‐maximum of symmetric (0002) diffraction as a function of GaInN thickness. This in situ XRD measurement enables to clearly observe the critical thicknesses corresponding to strain relaxation in the GaInN/GaN heterostructure caused by the formation of surface pits with bent threading dislocations and the generation of misfit dislocations on GaInN during growth. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)